2022
DOI: 10.1177/00027642221085885
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 Pandemic Impacted the Perception of Climate Change in the UK

Abstract: The COVID-19 pandemic erupted during the climate change (CC) crisis, forcing individuals to adapt abruptly to a new scenario, and triggering changes in everyone’s lifestyles. Based on a sample of the UK population ( N = 1013), this paper investigates how the COVID-19 pandemic invited/forced individuals to reflect upon a more sustainable way of life (which might be enhanced by the use of digital technologies for daily activities) and to (re)consider the anthropogenic impact on the environment. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…According to Ruiu et al [69], the COVID-19 pandemic invited individuals to reflect upon a more sustainable way of life and daily activities, tend to reconsider the anthropogenic impact on the environment and associate the COVID-19 pandemic with an opportunity to promote an eco-friendly world and to adopt an eco-sustainable approach using technology. However, the study is from the context of the UK population and did not explore the adoption of eco sustainable approach from the context of daily transport use behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ruiu et al [69], the COVID-19 pandemic invited individuals to reflect upon a more sustainable way of life and daily activities, tend to reconsider the anthropogenic impact on the environment and associate the COVID-19 pandemic with an opportunity to promote an eco-friendly world and to adopt an eco-sustainable approach using technology. However, the study is from the context of the UK population and did not explore the adoption of eco sustainable approach from the context of daily transport use behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies indicated that 75% of infectious diseases, including the COVID-19 pandemic, which has acute consequences for human health, originate from animals, mainly due to the misuse of biodiversity and climate change. It's time to transform how we engage with nature and climate because when we prioritize healthy ecosystems, we safeguard our own well-being [5,6,69].…”
Section: Transportation and The Covid-19 Pandemic In Addismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Urban and Kohlová's (2022) study found no uniform effect on the behavioral costs of pro-environmental behaviors, nor on green decision-making. The study of Ruiu et al (2022) showed that younger and more educated people, on average, see the COVID-19 epidemic as an opportunity to encourage pro-environmental behavior and embrace an eco-sustainable attitude. The results of Evensen et al (2021) revealed little sign of waning awareness about climate change during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Web of Science; November 2022) revealed that the topic of perception has not been well studied ( Sharifi, 2022 ). For instance, Büssing et al, 2020a , Büssing et al, 2020b studied the perceived changes of certain attitudes and Ruiu et al (2022) studied how the COVID-19 pandemic has impacted the perception of Climate Change in the UK though these studies generally remain specific to certain contexts and geographical regions.. The public awareness about these impacts offers an opportunity to develop effective future policies to protect the environment ( Mousazadeh et al, 2021 ; Soni and Mistur, 2022 ) and develop better urban planning ( Sharifi, 2022 ).…”
Section: Introductionmentioning
confidence: 99%